E-Learning Model for Equivalency Education Program in Indonesia - Mesra Betty Yel; Sfenrianto Sfenrianto (IAES Indonesia Section, 2017)
with the emergence of e-Learning, governments provide opportunities for online learning, whether formal or informal. However, most of e-learning systems in Indonesia have been used at formal education environments, today. Therefore, this study proposes an E-Learning model to support non-formal education in Indonesia. This model is called as E-learning for the Equivalency Education Program (E-LEEP) model. The E-LEEP consists of three components: User, Education Program, and Monitoring. The user will be students and tutor. The education program includes Package A, Package B, and Package C for elementary school, junior high school, and senior high school respectively. The monitoring will be used by institution and stakeholders. Each component will support the needs of students programs in e-Learning environment, in order to achieve the goal learning.